Introducing an intrateam longitudinal approach to the study of team process dynamics - Li, Jia; Roe, Robert A. (European journal of work and organizational psychology, 2012)
In this article, we introduce an intrateam longitudinal approach to study the temporal dynamics of team processes and its relations to antecedent and consequence variables. We compare this approach with the conventional interteam longitudinal approach (e.g., repeated-measures [M]ANOVA, random coefficient modelling, latent growth modelling) and discuss the conceptual and methodological differences between the two approaches. Whereas the interteam approach follows a sample-to-cases order of inference and assumes random deviances of individual teams' change patterns from the sample-level pattern, the intrateam approach follows a cases-to-sample order of inference and allows for qualitative differences in individual teams' change patterns. In the intrateam approach, each team's change trajectory is directly measured and then used in the next-step multivariate analyses. We argue that the intrateam approach is more compatible with the current conceptualization of team processes as team members' interactions over time (Marks, Mathieu, & Zaccaro, 2001) and with the reasoning underlying the Input-Process-Output (IPO) framework. Next, we illustrate the intrateam approach and apply both approaches in an empirical longitudinal study of team conflict and team satisfaction (N = 42). The results show the contrast between the two approaches and added value of the intrateam approach in the study of team process dynamics.